2019
DOI: 10.1039/c9pp00096h
|View full text |Cite
|
Sign up to set email alerts
|

Diphenylaminostyryl-substituted quinolizinium derivatives as fluorescent light-up probes for duplex and quadruplex DNA

Abstract: E)-2-[1'-((Diphenylamino)styryl)quinolizinium (3a) and 2,2'-{( phenylimino)-bis[(E)-1'',1'''-styryl]}-bis[quinolizinium] (3b) were synthesized, and their interactions with duplex DNA and quadruplex DNA were investigated with a particular focus on their ability to operate as DNA-sensitive fluorescent probes. Due to the significantly different size and steric demand of these quinolizinium derivatives they exhibit different binding modes. Thus, 3a intercalates into duplex DNA and binds through π stacking to quadr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 101 publications
0
13
0
Order By: Relevance
“…In contrast, the very low emission intensity of 3d did not change upon the addition of ct DNA. The fluorescence light-up effects of the ligands 3a-c upon association with DNA resembled the ones observed for other styryl-substituted quinolizinium derivatives [62][63][64][65][66][67]. Accordingly, the emission enhancement most likely resulted from the accommodation of the ligand in the constrained binding site of the DNA, which led to a restricted conformational flexibility.…”
Section: Dna-binding Propertiesmentioning
confidence: 57%
See 1 more Smart Citation
“…In contrast, the very low emission intensity of 3d did not change upon the addition of ct DNA. The fluorescence light-up effects of the ligands 3a-c upon association with DNA resembled the ones observed for other styryl-substituted quinolizinium derivatives [62][63][64][65][66][67]. Accordingly, the emission enhancement most likely resulted from the accommodation of the ligand in the constrained binding site of the DNA, which led to a restricted conformational flexibility.…”
Section: Dna-binding Propertiesmentioning
confidence: 57%
“…As the quinolizinium ion has been established as a versatile platform for the development of DNA intercalators [60], we identified styryl-substituted quinolizinium derivatives as a promising basis for the search for photoswitchable DNA binders based on the photocycloaddition-photocycloreversion equilibrium. In fact, some selected styrylquinolizinium derivatives have already been shown to bind to DNA [61][62][63][64][65][66][67], however, their photocycloaddition reaction and the propensity of the corresponding photodimers to release the DNA-binding ligand have not been reported so far. Herein, we report on the photochemical and DNA-binding properties of the selected styrylquinolizinium derivatives 3a-d and demonstrate their ability to operate as photoswitchable DNA ligands.…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, numerous other styryl derivatives were reported as efficient “light-up” probes for G4-DNA and RNA, validating the potential of this molecular scaffold (Fig. 1) [22,33,6063]. Nevertheless, the structural determinants for the desired properties of the probes (i.e., high selectivity for G4-DNA or G4-RNA with respect to double-stranded or single-stranded nucleic acids, high fluorimetric response and quantum yield, low background fluorescence) are still poorly understood, mostly due to the lack of comparative studies.…”
Section: Introductionmentioning
confidence: 82%
“…The spirooxazine-quinolizinium conjugates 3a and 3b were synthesized by the base-catalyzed reaction [60,62,64,65] of 2-methylquinolizinium (2a) [66,67] or coralyne (2b) [68] with the 5'-formyl-substituted spirooxazine 1b [48,49,69] (Scheme 2 Scheme 2: Synthesis of the spirooxazine-quinolizinium conjugates 3a and 3b. and Scheme S1, Supporting Information File 1).…”
Section: Synthesismentioning
confidence: 99%
“…For this purpose, we chose the quinolizinium ion as the cationic aryl substituent because it has been shown that derivatives thereof have a great potential to serve as functional units in DNA-binding ligands [54], fluorescent dyes and chemosensors [55][56][57][58][59]. Furthermore, we have already demonstrated that styryl-substituted quinolizinium derivatives exhibit ideal photophysical and DNA-binding properties to be used as DNA-sensitive fluorescent probes in cell imaging [60][61][62] or as photoswitchable DNA ligands [63]. Therefore, we were interested in a combination of the photochromic properties of the spirooxazine moiety with the advantageous photophysical and biological properties of the quinolizinium ion to develop photoswitchable functional quinolizinium derivatives.…”
Section: Introductionmentioning
confidence: 99%